Comparison between Variable and Conventional Volume-Controlled Ventilation on Cardiorespiratory Parameters in Experimental Emphysema - Henriques, Isabela; Padilha, Gisele A.; Huhle, Robert; Wierzchon, Caio; Miranda, Paulo J. B.; Ramos, Isalira P.; Rocha, Nazareth; Cruz, Fernanda F.; Santos, Raquel S.; de Oliveira, Milena V.; Souza, Sergio A.; Goldenberg, Regina C.; et al. (Frontiers in Physiology, 2016)
Emphysema is characterized by loss of lung tissue elasticity and destruction of structures supporting alveoli and capillaries. The impact of mechanical ventilation strategies on ventilator-induced lung injury (VILI) in emphysema is poorly defined. New ventilator strategies should be developed to minimize VILI in emphysema. The present study was divided into two protocols: 1) characterization of an elastase-induced emphysema model in rats and identification of the time point of greatest cardiorespiratory impairment, defined as a high specific lung elastance associated with large right ventricular end-diastolic area; and 2) comparison between variable (VV) and conventional volume-controlled ventilation (VCV) on lung mechanics and morphometry, biological markers, and cardiac function at that time point. In the first protocol, Wistar rats (n=62) received saline (SAL) or porcine pancreatic elastase (ELA) intratracheally once weekly for 4 weeks, respectively. Evaluations were performed 1, 3, 5 or 8 weeks after the last intratracheal instillation of saline or elastase. After identifying the time point of greatest cardiorespiratory impairment, an additional 32 Wistar rats were randomized into the SAL and ELA groups and then ventilated with VV or VCV (n=8/group) (tidal volume [VT]=6mL/kg, positive end-expiratory pressure [PEEP]=3cmH2O, fraction of inspired oxygen [FiO2]=0.4) for 2h. VV was applied on a breath-to-breath basis as a sequence of randomly generated VT values (mean VT=6 mL/kg), with a 30% coefficient of variation. Non-ventilated (NV) SAL and ELA animals were used for molecular biology analysis. The time point of greatest cardiorespiratory impairment, was observed 5 weeks after the last elastase instillation. At this time point, interleukin (IL)-6, cytokine-induced neutrophil chemoattractant (CINC)-1, amphiregulin, angiopoietin (Ang)-2, and vascular endothelial growth factor (VEGF) mRNA levels were higher in ELA compared to SAL. In ELA animals, VV reduced respiratory system elastance, alveolar collapse, and hyperinflation compared to VCV, without significant differences in gas exchange, but increased right ventricular diastolic area. Interleukin-6 mRNA expression was higher in VCV and VV than NV, while surfactant protein-D was increased in VV compared to NV. In conclusion, VV improved lung function and morphology and reduced VILI, but impaired right cardiac function in this model of elastase induced-emphysema.